Regulation of vascular endothelial growth factor in prostate cancer - de Brot, Simone; Ntekim, Atara; Cardenas, Ryan; James, Victoria; Allegrucci, Cinzia; Heery, David M.; Bates, David O.; Ødum, Niels; Persson, Jenny L.; Mongan, Nigel P. (Bioscientifica, 2015)
Prostate cancer (PCa) is the most common malignancy affecting men in the western world. Although radical prostatectomy and radiation therapy can successfully treat PCa in the majority of patients, up to ∼30% will experience local recurrence or metastatic disease. Prostate carcinogenesis and progression is typically an androgen-dependent process. For this reason, therapies for recurrent PCa target androgen biosynthesis and androgen receptor function. Such androgen deprivation therapies (ADT) are effective initially, but the duration of response is typically ≤24 months. Although ADT and taxane-based chemotherapy have delivered survival benefits, metastatic PCa remains incurable. Therefore, it is essential to establish the cellular and molecular mechanisms that enable localized PCas to invade and disseminate. It has long been accepted that metastases require angiogenesis. In the present review, we examine the essential role for angiogenesis in PCa metastases, and we focus in particular on the current understanding of the regulation of vascular endothelial growth factor (VEGF) in localized and metastatic PCa. We highlight recent advances in understanding the role of VEGF in regulating the interaction of cancer cells with tumor-associated immune cells during the metastatic process of PCa. We summarize the established mechanisms of transcriptional and post-transcriptional regulation of VEGF in PCa cells and outline the molecular insights obtained from preclinical animal models of PCa. Finally, we summarize the current state of anti-angiogenesis therapies for PCa and consider how existing therapies impact VEGF signaling.